시각장애인을 위한 의약품 및 알약 조회 모바일 어플리케이션 구현 - 김소은(So-Eun Kim); 위영은(Young-Eun Wi); 이종우(Jong-Woo Lee) (디지털콘텐츠학회논문지, 2023)
약사법에 따르면 의약품은 용기나 포장에 제품명, 사용기한, 용량 등의 사항을 기재해 올바르고 안전하게 사용할 수 있도록 해야 한다. 그러나 그러한 사항들이 점자로 표기된 경우는 극히 드물며 표시내용마저 부실하여 시각 장애가 있는 사람들은 의약품 정보를 정확하게 알고 복용하기 어렵다. 본 논문에서는 시각장애인이 음성 가이드를 기반으로 의약품을 편리하게 조회할 수 있도록 통합 서비스를 제공하는 모바일 어플리케이션을 구현한다. 용기 촬영, 낱알 촬영, 음성 인식, 처방전 촬영, 약 봉투 촬영과 같이 다양한 방법을 통해 의약품 조회가 가능하도록 하였으며, 낱알 조회에서는 CNN (Convolutional Neural Networks)을 기반으로 한 알약 인식 모델을 구축하였다. 결과적으로 시각장애인은 단순한 UI와 최소한의 입력을 통해 쉽게 의약품 정보를 얻을 수 있으며 이를 통해 시각장애인의 의약품 오용을 줄일 수 있을 것이다. According to the Pharmaceutical Affairs Act, medicines should be used correctly and safely by stating the product name, expiration date, and dosage on the container or packaging. However, such matters are rarely marked in braille, and the labeling is poor, making it difficult for visually impaired people to accurately know and take medication information. In this paper, we implement a mobile application that provides integrated services so that blind people can conveniently inquire about medicines based on voice guides. Medicines inquiry is possible through various methods such as container recognition, pill recognition, speech recognition, prescription recognition, and drug envelope recognition, and a CNN-based pill recognition model was also developed. Using our implementation, blind people can easily obtain medicines information through simple UI and minimal input, which will reduce drug misuse by blind people. KCI Citation Count: 0